Nanophotonic biosensors for point-of-care COVID-19 diagnostics and coronavirus surveillance. (15th January 2021) - Ruiz-Vega, Gisela; Soler, Maria; Lechuga, Laura M
Abstract: The COVID-19 pandemic has revealed the need of novel diagnostic technologies for rapid and accurate virus detection. In the European CONVAT project, a point-of-care nanophotonic biosensor is being developed for the direct, fast and specific identification of severe acute respiratory syndrome coronavirus 2 from both human patient samples and animal reservoirs. The technology will provide a quantitative detection of the viral load and it can be implemented in decentralized settings to improve the early diagnosis and clinical management of patients as well as coronavirus environmental monitoring to prevent future outbreaks.